فعّالية استخدام الحاسوب في تعليم اللغة العربية لتنمية مهارة الكلام بالصف التاسع ب بالمدرسة دار السلام جومبانج: Efektivitas Penggunaan Komputer dalam Pengajaran Bahasa Arab untuk Meningkatkan Keterampilan Bicara di Kelas IX B MTs Darussalam Jombang - Luthfi, Ibnu Mas'ud (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2024)
Therefore, facing similar problems, it becomes a necessity for teachers to be able to express their innovation and creativity to create and design teaching strategies that are more interesting and in line with needs and objectives so that they can create a more effective and enjoyable teaching and learning process, one the other is using computers as a teaching medium. Problem formulation: